2018
DOI: 10.1155/2018/6183162
|View full text |Cite
|
Sign up to set email alerts
|

RAPD PCR Profile, Antibiotic Resistance, Prevalence of armA Gene, and Detection of KPC Enzyme in Klebsiella pneumoniae Isolates

Abstract: The increasing prevalence of multidrug-resistant Klebsiella pneumoniae strains isolated from hospitals shows the limitation of recent antibiotics used for bacterial eradication. In this study, 81 K. pneumoniae isolates were collected from three hospitals in Tehran. Antibiotic susceptibility test showed the highest rates of resistance to cefotaxim (85.5%) and ceftazidime (78.3%), and the lowest rates of resistance were detected for colistin (16.9%), streptomycin (16.8%), and chloroamphenicol (21.7%). Eleven dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
5
12
2
Order By: Relevance
“…Moderate incidence of resistance (54%, 46%, and 40%) was exhibited for amikacin, tetracycline, and chloramphenicol, respectively, in this study. Such incidence is similar to previous reports 19,20 . Alternatively, 28% of our isolates were resistant to gentamycin; however, a higher percentage was reported by Farivar et al 19 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moderate incidence of resistance (54%, 46%, and 40%) was exhibited for amikacin, tetracycline, and chloramphenicol, respectively, in this study. Such incidence is similar to previous reports 19,20 . Alternatively, 28% of our isolates were resistant to gentamycin; however, a higher percentage was reported by Farivar et al 19 .…”
Section: Discussionsupporting
confidence: 93%
“…Such incidence is similar to previous reports 19,20 . Alternatively, 28% of our isolates were resistant to gentamycin; however, a higher percentage was reported by Farivar et al 19 . Finally, all isolates in this study were sensitive to colistin; in contrast, Farivar et al 19 reported a lower percentage (83%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Antibiotic resistance patterns exhibited by the Klebsiella pneumoniae isolates showed that 32 patterns were found with Ceftriaxone, Ciprofloxacin, Imipenem and Tetracycline being the most encountered. This finding agrees with the study of Arezoo et al (2018) who reported several resistance patterns. The different antibiotic resistance patterns observed is an indication of a widespread unregulated use of these antimicrobials coupled with factors such as sexual activity, age, sex, poor immunity, personal hygiene, history of recurrent UTI's, and social behaviour.…”
Section: Discussionsupporting
confidence: 93%